1996
DOI: 10.1007/pl00014240
|View full text |Cite
|
Sign up to set email alerts
|

The North American Maternal Phenylketonuria Collaborative Study, developmental assessment of the offspring: preliminary report

Abstract: Preliminary results of 2-year Bayley and 4-year McCarthy test scores are presented. To date numbers are too small to statistically correlate:- offspring from pregnancies in which diet was started prior to conception, offspring from pregnancies with phenylalanine (Phe) levels of 120-360 mumol/l versus 360-600 mumol/l, influence of home environment, influence of maternal nutrition, language development, behaviour/hyperactivity, Revised Wechsler Intelligence Score, school performance and learning disabilities. Tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The results of the volumetric measurements are summarized in Table 1. These findings of Pfaendner et al [13] are in accordance with other, nonquantitative imaging studies [8,[16][17][18][19]. However, it has not been previously reported that the size of the hippocampus is reduced in PKU.…”
Section: Mr Volumetrysupporting
confidence: 82%
“…The results of the volumetric measurements are summarized in Table 1. These findings of Pfaendner et al [13] are in accordance with other, nonquantitative imaging studies [8,[16][17][18][19]. However, it has not been previously reported that the size of the hippocampus is reduced in PKU.…”
Section: Mr Volumetrysupporting
confidence: 82%
“…Most such individuals are mentally normal and are now of child bearing age. Unfortimately, most of them have discontinued the PHErestricted diet since childhood and have high blood PHE levels Hanley et al, 1996). It is now clear that women with PKU not treated prior to conception are at increased risk of having a pregnancy that results in serious fetal damage.…”
Section: Clinical Management Of Pkumentioning
confidence: 99%
“…Table 3 presents data from a broader sample of the infants from the MPKUCS at 2 years of age. Among offspring whose mothers attained metabolic control by 20 weeks' gestation, the median DQ was within the average range, whereas the median DQ of offspring whose mothers were not in metabolic control until after 20 weeks' gestation was in the range of mental retardation [Hanley et al, 1996].…”
Section: The Maternal Pku Collaborative Studymentioning
confidence: 87%
“…Psychological data on only a small number of school-age subjects have been published [Hanley et al, 1996]. The mean IQ of maternal PKU offspring followed a similar pattern: 93 for offspring whose mothers attained metabolic control by 10 weeks; 88 for those whose mothers attained metabolic control between 10 and 20 weeks; and 73 for those whose mothers were not in control until after 20 weeks.…”
Section: The Maternal Pku Collaborative Studymentioning
confidence: 92%
See 1 more Smart Citation